The Effect of Gamma-Ray Irradiation on the Physical, Mechanical, and Morphological Characteristics of PVA-Collagen-Chitosan as a Guided Tissue Regeneration (GTR) Membrane Material - Komara, Ira; Susanto, Agus; Amaliya, Amaliya; Abbas, Basril; Warastuti, Yessy; Hendiani, Ina; Miranda, Aldilla; Erliani, Annisa Pranuditha (European Journal of Dentistry, 2022)
Objective The aim of this study was to evaluate the effect of gamma-ray irradiation on the physical, mechanical, and morphological characteristics of the polyvinyl alcohol (PVA)-collagen-chitosan membranes as a guided tissue regeneration membrane material.Material and Method The membrane was fabricated by mixing PVA, collagen, and chitosan using the film casting method. PVA-collagen-chitosan membranes were irradiated with various radiation dose (0, 15, and 25 kGy). Furthermore, it is characterized using Fourier-transform infrared (FTIR) for functional group identification, morphological test was performed using scanning electron microscopy (SEM), and mechanical properties (i.e., tensile strength and elongation) were evaluated using universal testing machine and swelling studies.Statistical Analysis Statistical analysis was performed based on analysis of variance and post hoc with p-value < 0.05.Result The FTIR spectrum shows various peaks of functional groups from the PVA-collagen-chitosan membrane. The result of the statistical analysis show changes in tensile strength (p = 0.0004) and membrane elongation (p = 0.000451) at different radiation doses of 0, 15, and 25 kGy. The membrane absorption obtains p-value of 0.0193, while the SEM results show that the PVA-collagen-chitosan membrane homogeneously mixed.Conclusion There is an effect of gamma-ray irradiation on tensile strength, elongation, and water absorption of the membranes. Increasing the radiation dose increases the value of tensile strength, while elongation and absorption of the membrane decrease. The PVA-collagen-chitosan membrane has the potential to develop as an alternative membrane for guided tissue regeneration.
Keywords: gamma irradiation; guided tissue regeneration; polyvinyl alcohol (PVA)